Using of Case Technology in Educational Systems as an Interactive Method - Laylo Gulomjonovna Sattorova, (Indonesian Journal of Innovation Studies, 2022)
The case study method (analysis of specific situations) is one of the options for applying modern pedagogical technologies in the practice of education aimed at solving the problems of the SES. Analysis of specific learning situations (case study) is a teaching method designed to improve skills and gain experience in the following areas: identifying, selecting and solving problems; work with information - understanding the meaning of the details described in the situation; analysis and synthesis of information and arguments; work with assumptions and conclusions; evaluation of alternatives; making decisions; listening and understanding other people are group work skills.